Hypothyroidism with Myxedema Coma Complications: A Review of Articles during November 2024 - Paramadinda, Ni Made Ayu Mas Sista; Aulia, Siti Zahroni; Rahmawati, Fadila; Yuar, Alana Akmal; Valencia, Perlin Nigel; Qadri, Annisa Salsabila; Rabbani, Yaskuna Urfi; Hakim, Baiq Sheila Oktalia; Yolanda, Rizki; Wibawa, Galang Edi (Jurnal Biologi Tropis, 2025)
Hypothyroidism is a condition characterized by decreased thyroid hormone production due to impaired thyroid or hypothalamic-pituitary gland function. Hypothyroidism is more common in women due to iodine deficiency. This condition can also be caused by autoimmune disorders. Symptoms of hypothyroidism vary, from mild, with few or no symptoms, to severe. Most symptoms are variable, vague, and delayed in onset. This paper aims to provide a comprehensive understanding of the diagnosis and management of hypothyroidism complicated by myxedema coma. The writing method used in this literature review is references from various Indonesian and English-language literature. The literature search was conducted during November 2024, with 10 articles obtained. The review results showed that severe and uncontrolled hypothyroidism can lead to myxedema coma. Myxedema coma is a condition characterized by decreased consciousness accompanied by generalized edema. This condition frequently associated with hypothermia and hyponatremia. Myxedema coma can be diagnosed using a scoring system. Therefore, an understanding of how to diagnose and properly manage hypothyroidism with complications of myxedema coma is needed for early detection so as not to worsen the patient's prognosis.